Protests, space and creativity: theatre as a site for the affective construction of democracy in Nepal - Mottin, Monica (Political change and public culture in post-1990 Nepal, 2017)
IntroductionAarohan Theatre artists are professional performers when interpreting stage dramas at Sama Theatre in Gurukul or kachahari natak (the Nepali adaptation of Augusto Boal's Forum Theatre) along the streets or in the schools of Kathmandu. However, when playing loktantrik natak (theatre for democracy), a form of political-street theatre, emerged during the protests that led to the 2006 Jan Andolan II (People's Movement), their role doubled. As both theatre and social actors, Aarohan artists also played themselves as Nepali citizens fighting for democracy. Their dramas aimed at transforming reality.Anya Peterson Royce talks about the interpretative role of the performing arts and of the requisite ‘technical mastery, virtuosity and artistry that make that role possible and transformative’ (2004, 1). But there is more in performing arts than interpretation and representation, in particular in the specific form that loktantrik natak took during the Citizen's Movement for Democracy and Peace (CMDP) in Nepal. The artists’ experience shows that a performance is not only an ‘ideological transaction’ (Kershaw, 1992) but also and indeed an affective one. The emotions conjured up by Aarohan's dramatic performances in the streets, as well as by other artistic protest forms that I will mention later, helped co-create an affective space for the Citizen's Movement to develop and sustained the protesters’ struggles, as many studies on the role of emotions in social movements demonstrate (Goodwin, Jasper and Polletta, 2001; Jasper, 2011). Thus, the aesthetics of loktantrik natak challenge hermeneutic and semiotic aesthetics. The theatrical performance becomes a ‘site’, intended as ‘an active and always incomplete incarnation of events, an actualization of times and spaces that uses the fluctuating conditions to assemble itself’ (Kwon, 2004 cited in Thrift, 2008, 12), where ‘newness’ (Liep, 2001) - in this case the imagination and feeling of a new democratic order - could emerge.By analysing the work of Aarohan Theatre Group this chapter aims to provide an insight into the role of cultural activism during the 2005 Emergency and the period that followed till after the April 2006 Jan Andolan II.
Gesehen am 03.05.2023